Night Sleep, Parental Bedtime Practices and Language Development in Low-Risk Preterm and Full-Term Late Talkers: A Longitudinal Study in the Third Year of Life - Mariagrazia Zuccarini; Martina Riva; Arianna Aceti; Luigi Corvaglia; Anat Scher; Annalisa Guarini; Alessandra Sansavini (MDPI AG, 2024)
Background: Studies on night sleep and parental bedtime practices and their associations with language development in populations at risk of language delay and neonatal conditions, such as late talkers and preterm children, are scarce. Objectives: Our objective was to longitudinally examine the development of night sleep (total night sleep difficulties, settling, night waking, and co-sleeping), parental bedtime practices (total parental bedtime practices, active physical comforting, encouraging autonomy, and leaving to cry), and expressive language (word and sentence production), and their associations in low-risk preterm and full-term late talkers from 31 to 37 months of age. Methods: Parents of 38 late talkers, 19 low-risk preterm and 19 full-term children, completed the Italian versions of the Infant Sleep Questionnaire, the Parental Interactive Bedtime Behavior Scale, and the MacArthur-Bates Communicative Development Inventory Words and Sentences Long Form. Results: Late talkers' night sleep difficulties, such as settling to sleep and night waking, decreased over time, with low-risk preterm late talkers experiencing more night waking and co-sleeping than full-term peers. Parents reported that instances of active physical comforting and leaving to cry also decreased, with parents of low-risk preterm late talkers reporting higher active physical comforting scores than parents of full-term peers. Improvements in parental practices of encouraging autonomy were significantly associated with increased sentence production from 31 to 37 months. Conclusions: Findings highlight the importance of monitoring night sleep in preterm and full-term late talkers. They also suggest that populations vulnerable to sleep and language delays may particularly benefit from targeted interventions promoting autonomy in their bedtime routines, which, in turn, could support their language development trajectories.